Transformation Of The Tahfīdz Tradition In Indonesia: Between Traditional And Contemporary Education - Mahmud Hibatul Wafi; M. Nurzen S; M. Beni Saputra; M. Munawir Pohan; Ade Putra Hayat (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Quran memorization education in Indonesia has recently experienced significant developments, both in terms of style and method. This indicates a shift in the perception of the Muslim community towards tahfidz education. This study aims to reveal the transformation of tahfidz education in Indonesia and the changes in people's perspective on tahfidz tradition. This research focuses on two Islamic educational institutions, namely the National Quran Tahfidz Quarantine Foundation as a representation of contemporary tahfidz education and Pondok Pesantren Tahfidz Yanbu’ al-Qur’an Kudus as a representation of contemporary tahfidz education. This research uses a descriptive-qualitative approach, while data sources come from various literatures, including books, journal articles, and internet media. While the data analysis technique used is descriptive-analytic. This study found that between tahfidz education in Yanbu’ al-Qur’an and the National Quran Tahfidz Quarantine Foundation there are very contrasting differences both in terms of methods and learning orientation. The difference indicates the transformation of tahfidz tradition from classical to modern (method) and oriented towards the fulfillment of identity. In addition, the transformation of tahfidz tradition is influenced by the new trend of Islamism, especially among urban communities who position tahfidz as a standard of piety.